CTNI-22. RETROSPECTIVE ANALYSIS OF THE COMBINED TREATMENT OF VINCRISTINE, ACNU, CARBOPLATIN AND INTERFERON-β PLUS RADIOTHERAPY (VAC-FERON-R)IN PATIENTS WITH DIFFUSE ASTROCYTOMA - Arakawa, Yoshiki (Neuro Oncol, 2020)
OBJECTIVE: Diffuse astrocytomas are classified as WHO grade II and its median overall survival (mOS) is 10 to 11 years. The efficacy of chemoradiation in the high-risk feature has been reported. The prognosis is associated with IDH and TERT promoter (TERTp) mutations. Here, we retrospectively analyzed the patients with diffuse astrocytoma treated with vincristine, ACNU, carboplatin and interferon-β plus radiotherapy (VAC-feron-R)in our institute. PATIENTS AND METHODS: Between December 2003 to January 2016, 44 patients were diagnosed as diffuse astrocytoma with integrated diagnosis of histological and molecular analysis. The average age was 43.1 years (22–71 years). They received VAC-feron-R as initial treatment in our institute. We analyzed the IDH1/2 and the TERTp mutation using Sangar sequencing and determined the 1p/19q codeletion by the fluorescence in situ hybridization or the multiplex ligation-dependent probe amplification. RESULTS: Median follow-up period was 76.5 months, mPFS was 126 months, mOS did not reach, and 10-year survival rate was 60%.IDH status was determined in 29 patients, 9 mutant and 20 wild types. There was no significant difference in PFS and OS between the two groups. TERTp status was determined in 18 patients with IDH wild type, 6 mutant and 12 wild types. mPFS of patients with TERTp wild type did not reach, but that with TERTp mutant type was 34.5 months (p = 0.0356). CONCLUSION: Compared with previous clinical studies, VAC-feron-R showed a favorable clinical outcome in diffuse astrocytoma. The impact of TERTp status on prognosis was identified but not IDH status in this cohort.